KAJIAN KESETIMBANGAN AIR DAN EVALUASI POLA TANAM PADA DAERAH IRIGASI MEDAS: Water Balance Analysis and Cropping Pattern Evaluation in Medas Irrigation Area - Saidah, Humairo; Salehudin, Salehudin; Putri, Utami Meiliani (Ganec Swara, 2025)
Water balance refers to the analysis of water inputs and outputs at a specific location over a defined period of time. This study aims to provide an overview of the water balance in the Medas Irrigation Area with respect to the existing cropping pattern practiced by the community, namely Paddy–Paddy–Palawija. The research employed a quantitative descriptive method, applying the FAO Modified Penman method to estimate potential evapotranspiration and a simple water balance approach for the water balance analysis for any hydrological condition. The results indicate that the Medas Irrigation Area faces a high risk of water shortage in dry years, with almost all months experiencing a deficit except December. In normal years, the risk is classified as moderate, with deficits occurring during the dry season (May–October). In contrast, in wet years, there is no risk of failure, as all months show a surplus.